If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = x + 26 Reorder the terms: -4 + 7x = x + 26 Reorder the terms: -4 + 7x = 26 + x Solving -4 + 7x = 26 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 7x + -1x = 26 + x + -1x Combine like terms: 7x + -1x = 6x -4 + 6x = 26 + x + -1x Combine like terms: x + -1x = 0 -4 + 6x = 26 + 0 -4 + 6x = 26 Add '4' to each side of the equation. -4 + 4 + 6x = 26 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 26 + 4 6x = 26 + 4 Combine like terms: 26 + 4 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 3-.2y-1.4y=-9.2 | | -6(x-2)=24 | | 2(x-3)-17=13-3(x+20) | | 18y-11=76 | | 3(v+8)+6= | | (3x+8)=180 | | (9-z)(2z+7)=0 | | -6(x+2)=24 | | 44+30x=99+25x | | -5+5x=5(x+1) | | -6(x+12)=24 | | x+(x+1)=12 | | (5x+4y)=x | | 2x-8x+1=-10x | | 6x+3(-3x+2)= | | (5x+4y)=180 | | -5+5=5(x+1) | | 5x-8x+10=2x+25 | | 6=a+3+2 | | .5x+6=-4 | | 2n+2=-196 | | 4(2+2n)-4= | | -6=2y-2/5 | | 7k^2+13k+2=0 | | -7+2(n-7)= | | z+(-45)=-50 | | 3x^2+6x+x+2= | | 5(x+2)=4x+17 | | 5+x=2x | | (w+3)2=2w^2-4w+33 | | 2x-3=6+7x | | x+(x+7)+(2x+1)=180 |